Pacifism, Politics, and Feminism Intersections and Innovations - Kling, Jennifer (Value Inquiry Book Series, 2019)
This anthology explores the many and varied connections between pacifism, politics, and feminism. Each topic is often thought about in academic isolation; however, when we consider how they intersect and interact, it opens up new areas for discussion and analysis.; Readership: All interested in social and political philosophy, ethnic and gender studies, and peace studies, and anyone concerned to understand their interrelations in order to create a more just, peaceful world.